2013
DOI: 10.1371/journal.pone.0064719
|View full text |Cite
|
Sign up to set email alerts
|

Local Applications of Myostatin-siRNA with Atelocollagen Increase Skeletal Muscle Mass and Recovery of Muscle Function

Abstract: BackgroundGrowing evidence suggests that small-interfering RNA (siRNA) can promote gene silencing in mammalian cells without induction of interferon synthesis or nonspecific gene suppression. Recently, a number of highly specific siRNAs targeted against disease-causing or disease-promoting genes have been developed. In this study, we evaluate the effectiveness of atelocollagen (ATCOL)-mediated application of siRNA targeting myostatin (Mst), a negative regulator of skeletal muscle growth, into skeletal muscles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 37 publications
1
23
0
Order By: Relevance
“…We found that local and systemic administration of the myostatin‐targeting siRNA delivered by ATCOL led to marked stimulation of muscle growth in vivo within a few weeks (Kawakami et al . , ).…”
Section: Introductionmentioning
confidence: 99%
“…We found that local and systemic administration of the myostatin‐targeting siRNA delivered by ATCOL led to marked stimulation of muscle growth in vivo within a few weeks (Kawakami et al . , ).…”
Section: Introductionmentioning
confidence: 99%
“…ATCOL-based delivery of siRNA resulted in efficient inhibition of metastatic tumors in vivo (15,16). We have also reported that 2-wk treatment with ATCOL-based myostatin-targeting siRNA (MstnsiRNA/ATCOL) increased muscle mass and enhanced muscle activity (17)(18)(19). These findings suggest that the delivery of Mstn-siRNA/ATCOL into skeletal muscle is safe, efficient, and effective for augmentation of muscle structure and function.…”
mentioning
confidence: 84%
“…Elevenweek-old C57BL/6 male mice were housed under a 12/12 h light/dark cycle and ambient temperature of 22˚C, and were provided with food and water ad libitum. On the basis of previous reports (12,(17)(18)(19)21), 10 M of Mstn-siRNA/ATCOL and 1 M of human ActRIIB-Fc fusion protein, purchased from Koken and R&D Systems Inc. (Minneapolis, MN), were used in this study. They were injected together into the left masseter muscles of the mice at 0 and 4 d. The control mice received injections of sterilized phosphate-buffered saline (PBS) into the left masseter muscles.…”
Section: Methodsmentioning
confidence: 99%
“…siRNA against myostatin, a gene that impedes muscle growth, delivered at a dose of 0.5 nmols from atelocollagen nanoparticles was shown to increase muscle growth, size, and activity in a mouse model of muscular dystrophy 147, 148 . These results were achieved via a local injection into mouse masseter muscle; however, the proven impact of myostatin siRNA on muscle growth motivates its further exploration in controlled delivery depots to regenerate weak or otherwise compromised muscle tissue.…”
Section: Therapeutic Applicationsmentioning
confidence: 99%